Inovasi Pengembangan Metode Tilawati Sebagai Solusi Kesulitan Membaca Al-Qur’an Pada Anak - Muhammad Sigit Muthahhari; Fakhri Abdullah Mundzir; Dina Mardiana (Jayapangus Press, 2026)
This study examines the innovative development of the Tilawati method in response to Qur’anic reading difficulties among junior high school students. Using a descriptive qualitative approach, the research was conducted through field observations, semi-structured interviews, and documentation at SMP Muhammadiyah 8 Bandung, with SMP ITQAN Islamic School Bandung used as a reference for good practice. The findings indicate that students’ reading difficulties are related not only to technical aspects, such as tajwid, makhraj, fashohah, rhythm, and fluency, but also to learning motivation, instructional time, teacher competence, and the availability of supporting media. The study identifies four main directions for developing the Tilawati method: strengthening teacher competence, grouping students according to reading ability, integrating varied and digital learning media, and building a Qur’anic culture within the school environment. The scientific contribution of this study lies in formulating a contextual development framework for the Tilawati method at the junior high school level, which combines classical talaqqi-based learning with adaptive, differentiated, and media-supported instructional strategies. The study concludes that the Tilawati method has the potential to support more effective Qur’anic learning when implemented consistently and aligned with students’ needs and institutional support.